2023
DOI: 10.1155/2023/1135733
|View full text |Cite
|
Sign up to set email alerts
|

Do Mechatronic Poles Change the Gait Technique of Nordic Walking in Patients with Ischemic Heart Disease?

Abstract: The study aimed to compare the technique of normal gait with the Nordic walking (NW) gait with classical and mechatronic poles in patients with ischemic heart disease. It was assumed that equipping classical NW poles with sensors enabling biomechanical gait analysis would not cause a change in the gait pattern. The study involved 12 men suffering from ischemic heart disease (age: 66.2 ± 5.2 years, body height: 173.8 ± 6.74 cm; body mass: 87.3 ± 10.89 kg; disease duration: 12.2 ± 7.5 years). The MyoMOTION 3D in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Weakness of the calf muscles causes dysfunction of this joint and, thus, a decrease in the "propelling force" of gait, which results, among others, in a decrease in speed 18,19 . Gait speed, stride length, gait cycle and step length are also lower in these patients compared to healthy individuals 20,21 . However, in previous studies, the authors did not refer to the NW gait technique, nor did they precisely describe at what level, according to the International Nordic Walking Federation (INWA) guidelines, the training programs were conducted based on kinematic and spatiotemporal parameters.…”
Section: Introductionmentioning
confidence: 72%
“…Weakness of the calf muscles causes dysfunction of this joint and, thus, a decrease in the "propelling force" of gait, which results, among others, in a decrease in speed 18,19 . Gait speed, stride length, gait cycle and step length are also lower in these patients compared to healthy individuals 20,21 . However, in previous studies, the authors did not refer to the NW gait technique, nor did they precisely describe at what level, according to the International Nordic Walking Federation (INWA) guidelines, the training programs were conducted based on kinematic and spatiotemporal parameters.…”
Section: Introductionmentioning
confidence: 72%
“…Secondly, we asked all participants to wear comfortable clothing and shoes during the testing session to minimise any additional effects on their gait pattern. Finally, we acknowledge that previous studies [30,31] and our own studies [32,33] have shown that the presence of IMU sensors does not interfere with natural movement nor alter gait patterns, and any differences in joint angle measurement can be attributed to the variability in the anatomical models used for calculations. The MyoMOTION MR3 sensors used in our study are small, lightweight, and wireless and are attached directly to the body and poles.…”
Section: Limitations Of the Conducted Studymentioning
confidence: 81%
“…These aspects of the impact of the system were investigated and analyzed by the authors. The results are presented in papers [27][28][29], demonstrating the lack of negative impact of the developed MNW system on NW gait patterns.…”
Section: Data Availability Statementmentioning
confidence: 95%